Pelatihan dan Bimbingan Metode Perbaikan dan Perawatan Mesin Outboard pada Nelayan di Desa Topejawa, Takalar - Faisal Mahmuddin; Syerly Klara; Muhammad Banda Selamat; Surya Hariyanto (Faculty of Engineering UNHAS, 2022)
The high cost of repair and maintenance of outboard engines is one of the big problems experienced by fishermen, their lack of knowledge about engine repair and maintenance results in them having to spend more money for their repair and maintenance costs. For this reason, the purpose of this service program is to train and guide the community on outboard engine repair and maintenance methods. The activity was carried out on August 21, 2021 in Topejawa Village, Mangarabombang District, Takalar Regency. This activity involved more than 20 participants from 2 (two) fishermen groups in Topejawa Village, Takalar. This activity was held in the coastal area of ​​Topejawa Village and was opened directly by the Representative of the Marine and Fisheries Service of the Takalar Government. From the results of the qualitative analysis, it was found that before the activity was carried out, the understanding of the community/partners of the working principle and machine operation, as well as machine maintenance and repair techniques were in the range of 30-50%. After that, the proportion of people's understanding increased by 75-90%. In addition, the fishermen also save on the cost of repairing and maintaining boat engines, which in turn increases the productivity and welfare of the fishing community, especially in the place where activities was carried out.